2010
DOI: 10.1021/la1040882
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme:Nanoparticle Bioconjugates with Two Sequential Enzymes: Stoichiometry and Activity of Malate Dehydrogenase and Citrate Synthase on Au Nanoparticles

Abstract: We report the synthesis and characterization of bioconjugates in which the enzymes malate dehydrogenase (MDH) and/or citrate synthase (CS) were adsorbed to 30 nm diameter Au nanoparticles. Enzyme:Au stoichiometry and kinetic parameters (specific activity, kcat, KM, and activity per particle) were determined for MDH:Au, CS:Au, and three types of dual-activity MDH/CS:Au bioconjugates. For single-activity bioconjugates (MDH:Au and CS:Au), the number of enzyme molecules adsorbed per particle was dependent upon the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 69 publications
3
73
0
Order By: Relevance
“…There is also the possibility of nonspecific adsorption between enzymes, which can have a negative effect on the active site conformation, resulting in decreased activity, as observed in this study. Previous studies conducted with simultaneous adsorption of MDH and CS on gold nanoparticles suggested interactions between enzymes in solution before immobilization . With sequential immobilization, there is improved control over the enzyme loading, which can be quantified, and a reduced effect of enzyme folding/unfolding on hydrophobic surfaces by the presence of other enzymes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also the possibility of nonspecific adsorption between enzymes, which can have a negative effect on the active site conformation, resulting in decreased activity, as observed in this study. Previous studies conducted with simultaneous adsorption of MDH and CS on gold nanoparticles suggested interactions between enzymes in solution before immobilization . With sequential immobilization, there is improved control over the enzyme loading, which can be quantified, and a reduced effect of enzyme folding/unfolding on hydrophobic surfaces by the presence of other enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the strategies developed for the study of substrate channeling are based on spatial organization on supports that require complex syntheses. In addition, studies involving the immobilization of malate dehydrogenase (MDH) and citrate synthase (CS) showed that there was decreased specific activity caused by enzyme structural changes . There is a lack of understanding of enzyme structural changes and conformations that can enhance activity and substrate channeling.…”
Section: Introductionmentioning
confidence: 99%
“…Attachment to a support minimizes unwanted interactions between enzyme molecules. In contrast, a combination of free enzymes in solution can result in unproductive interactions, as has been demonstrated for lipase–trypsin53 and malate dehydrogenase–citrate synthase 54…”
Section: Immobilized Enzymes For the Synthesis Of Drugs And Intermedimentioning
confidence: 99%
“…In many cases, these enzymes are embedded to restrict their diffusion [18], [19]; in other cases, the enzymes are truly tethered, usually via chemical attachment strategies. Building upon these advancements, there is growing interest in rebuilding entire biological pathways on hybrid systems [20], [21].…”
Section: Introductionmentioning
confidence: 99%